Standard Heparin Enhances the Antithrombotic Activity of Dermatan Sulfate in the Rabbit but CY 216 Does Not - Cadroy, Y; Dol, F; Caranobe, C; Petitou, M; Lormeau, J C; Sié, P; Choay, J; Boneu, B (Thrombosis and Haemostasis, 1988)
Standard heparin (SH) and dermatan sulfate (DS) two gly- cosaminoglycans with different pharmacological targets are effective antithrombotic agents in the rabbit. We have investigated the antithrombotic activity of the association DS plus SH. It was found that doses as low as 25 µg/kg for DS and 10 µg/kg for SH were ineffective when injected separately but generated a high and significant antithrombotic activity when injected together. These results were confirmed when higher doses of each compound were delivered in association. Further experiments were performed to determine if the enhancement of the antithrombotic activity of DS by HS resulted from its anti-factor Ha or antifactor Xa activity or from its moiety without affinity to AT III. A low molecular weight heparin (CY 216) with an anti-factor Xa/ anti-factor Ha ratio of 5, the synthetic pentasaccharide bearing the minimum binding sequence to antithrombin III, and a low affinity fraction of SH to AT III did not increase the antithrombotic activity of DS; in contrast a high affinity fraction of SH to AT III had the same effect than SH. We conclude that the enhancement of the antithrombotic activity of DS by SH mainly results from its anti-factor IIa activity.
Keywords: Heparin; Heparin derivatives; Dermatan sulfate; Thrombus prevention